Persepsi Pasien tentang Kualitas Layanan Mempengaruhi Kepuasan Pasien Rawat Inap Kelas III Rumah Sakit - Sulistyaningsih Sulistyaningsih; Fitnaningsih Endang Cahyani; Nuli Nuryanti Zulala; Sri Lestari (Universitas Ahmad Dahlan, 2020)
Background: The higher quality of hospital services will cause customers to have a high level of satisfaction and behavior. The purpose of the study was to analyze the quality of hospital inpatient services. Method: The survey research method used cross-sectional design. The sample of this study was 172 third class inpatients in PKU Muhammadiyah Gamping Hospital determined by consecutive sampling. Results: The results of study showed that patients' perceptions about the quality of inpatient services were mostly good on all dimensions (58%), most patients feel satisfied (63%). Conclusion: Education is significantly related to patients' perceptions of the quality of the hospital inpatient services. The experience of patients being treated in hospital is significantly related to inpatient satisfaction. Patients' perceptions of the quality of hospital inpatient services are significantly related to patient satisfaction. The quality dimension that needs to be improved is empathy, while the best is reliability.